2022
DOI: 10.3892/mmr.2022.12844
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA regulates expression of glucose transporter 1 via activation of the HIF‑1α signaling pathway

Abstract: Tanshinone IIA (Tan 2A) is a lipid-soluble compound extracted from the Chinese herb Danshen (Salvia miltiorrhiza Bunge). It protects neuron and microvascular endothelial cells against hypoxia/ischemia both in vitro and in vivo however the mechanism is not fully known. Glucose transporter 1 (GLUT-1) is ubiquitously expressed in all types of tissue in the human body and serves important physiological functions due to its glucose uptake ability. The present study evaluated the role of Tan 2A in regulating GLUT-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In terms of energy metabolism, the network pharmacology study showed that 17 absorbed constituents including salvianolic acids A, B, and C and tanshinone II A can act on the HIF-1 signaling pathway. In endothelial cells, tanshinone II A increased the mRNA level of GLUT-1, which promoted the activation of the HIF-1α signaling pathway, leading to enhanced glucose uptake [31]. In terms of cell apoptosis, ischemia, hypoxia, inflammation, and oxidative stress caused by atherosclerosis can all induce apoptosis, while excessive apoptosis further aggravates atherosclerosis [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of energy metabolism, the network pharmacology study showed that 17 absorbed constituents including salvianolic acids A, B, and C and tanshinone II A can act on the HIF-1 signaling pathway. In endothelial cells, tanshinone II A increased the mRNA level of GLUT-1, which promoted the activation of the HIF-1α signaling pathway, leading to enhanced glucose uptake [31]. In terms of cell apoptosis, ischemia, hypoxia, inflammation, and oxidative stress caused by atherosclerosis can all induce apoptosis, while excessive apoptosis further aggravates atherosclerosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro experiment, FDT demonstrated a significant inhibitory effect on platelet aggregation in a dose-dependent manner [9]. In a mouse model of Alzheimer's disease induced by Aβ [25][26][27][28][29][30][31][32][33][34][35] , the oral administration of FDT (0.81 g/kg, 3 weeks) was found to significantly reduce neuroinflammation by inhibiting the TNF-α and IL-6 levels [12]. Salvianolic acid B, a major bioactive constituent of Dan-Shen, mitigated myocardial infarction size by upregulating B cell lymphoma 2 (Bcl-2) and upregulating Bcl-2-associated X (Bax), caspase 3, c-Jun N-terminal kinase (JNK), and p38 expression in a mouse model of myocardial ischemia/reperfusion injury [13].…”
Section: Introductionmentioning
confidence: 99%